Sexual and asexual propagation of red elm (Ulmus rubra), grey alder (Alnus incana), and buffaloberry (Shepherdia canadensis) - Morales Rivera, Brenda Michelle (Kansas State University, 2012)
Red elm (Ulmus rubra), grey alder (Alnus incana and A. incana spp. tenuifolia) and buffaloberry (Shepherdia canadensis) are considered important plants for many Native American tribes in the United States. Native Americans have used these three species for a variety of medicinal uses and ceremonial purposes. Currently, Kansas tribal leaders would like to plant more of these species on tribal land, but the plants have been difficult to propagate. While red elm is valued as a ceremonial tree, it is susceptible to Dutch Elm Disease caused by the fungus (Ophiostoma ulmi) and is not grown in many ornamental nurseries. This has led to declining tree populations. The objective of these studies were to evaluate methods to propagate red elm, grey alder and buffaloberry in order to find techniques that can lead to an increase in the production of these species commercially and enable tribes and landowners to increase the presence of these native plants on their lands. In the first study, the use of gibberellic acid (GA3) was investigated to determine the optimum concentration needed for maximum seed germination. Studies were conducted with stratified (cold, moist storage) and non-stratified red elm, grey alder, and buffaloberry seeds soaked in one of four treatments: 0, 250, 500 or 1000 ppm of GA3 in 2010, and 0, 500, 1000, 2000 ppm of GA3 in 2011. Results indicate the use of GA3 in high concentrations promoted germination of unstratified seeds of red elm, though low seed viability in grey alder and buffaloberry resulted in poor germination. In a second study, vegetative cuttings were treated with potassium indole-3-butyric acid (K-IBA) and Dip ‘N GrowTM containing indole-3-butyric acid and naphthalene acetic acid (IBA + NAA). Softwood cuttings for the three species were treated with K-IBA and Dip ‘N GrowTM (plant rooting hormones): K-IBA at 5,000 and 10,000 ppm and Dip ‘N GrowTM at 1:10 ratio solutions. Results of this study showed that only grey alder softwood cuttings had callus formation, root growth, and shoot growth while red elm and buffaloberry did not respond to cutting propagation treatments.
Keywords: Propagation; Red elm; K-IBA; Giberrellic acid; Horticulture (0471)